PELATIHAN DAN PENDAMPINGAN MASTER OF CEREMONY (MC) PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA DAN DAERAH UPMI - Putu Dessy Fridayanthi; Gusti Ayu Made Puspawati (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2021)
Public speaking is communication that is done orally about a thing or topic in front of many people with the aim of influencing, inviting, educating, changing opinions, providing explanations, and providing information to many people at certain moments. Become a successful Master of Ceremony (MC); need to know aspects including voice (vocal), mental, appearance, insight. The MC training was attended by 25 students of the Indonesian Language Education Study Program and the UPMI Region. The methods of implementing Community Service are the socialization method, the test method, the lecture method, the training method, and the guidance method. The workshop materials on the Master of Ceremony (MC) are: Introduction to Public Speaking, Communication Skills, Basics of MC, Preparation before and during MC, Techniques for managing vocals, and Stages in MC. Based on the results of observations during the activity, it can be concluded that the material given to the training participants was well received, and the response given was very positive. The results of this service activity are participants 1) understand the basics and techniques of MC, 2) know and understand the requirements, duties and ethics of MC, 3) practice MC in opening, guiding the event until closing formal events, 4) being able to guide the event and display self-image according to the theme and script of the event, and 5) arrange vocals and personal appearance according to the demands of the event.